Polishing methods for composites restoration: the influence on human gingival fibroblasts behaviour - Benedetta Ghezzi; Matteo Meglioli; Andrea Salvaterra Toffoli; Giovanni Mergoni; Francesca Rossi; Maddalena Manfredi; Simone Lumetti; Edoardo Manfredi (BMC, 2024)
Abstract Background Carious/Non-carious cervical lesions with gingival recessions may require both dental and periodontal reconstructive therapy, where flaps/grafts may be placed in contact with a dental filling material. Human Gingival Fibroblasts (HGF-1) response during the early phase of healing could vary according to the procedures employed to cure the dental composite. Moreover, oxygen diffusion into dental composite inhibits the polymerization reaction, creating an oxygen-inhibited layer (OIL) that presents residual unreacted monomers. The aim of this study was to assess the effect of different polishing techniques and OIL on HGF-1. Methods Composite discs polished with different techniques (diamond rubber, abrasive discs and tungsten carbide burr) were used. An additional not polished smooth group obtained with and without OIL was used as control. Samples were physically characterized through the analysis of their hydrophilicity and surface topography through contact angle measurement and SEM, respectively; afterwards the biologic response of HGF-1 when cultured on the different substrates was analyzed in terms of cytotoxicity and gene expression. Results The finishing systems caused alterations to the wettability, even if without a proportional relation towards the results of the proliferation essay, from which emerges a greater proliferation on surfaces polished with one-step diamond rubber and with abrasive discs as well as a direct effect of the glycerin layer, confirming that surface roughness can heavily influence the biological response of HGF-1. Conclusions Surfaces wettability as well as cellular behavior seem to be affected by the selection of the finishing system used to lastly shape the restoration. Especially, the presence of OIL act as a negative factor in the regards of human gingival fibroblasts. The present study may provide the first clinical instruction regarding the best polishing system of composite material when the restoration is placed directly in contact with soft tissue cells. Understanding HGF-1 behavior can help identifying the polishing treatment for direct restoration of carious/non-carious cervical lesions associated with gingival recessions.